1998
DOI: 10.1046/j.1365-2281.1998.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head‐upright tilt on the dynamic of cerebral autoregulation

Abstract: The effect of head-upright tilting on the rate of cerebral autoregulation was studied in 12 healthy volunteers (nine men and three women; age range 20-36 years). The dynamics of cerebral autoregulation was determined from the rate of change in cerebral resistance (RoR) during a drop in arterial blood pressure induced by rapid deflation of a 3-min ischaemic thigh cuff and from the ratio of changes in cerebral blood flow and arterial blood pressure (CAI) during the recovery period after the drop in arterial bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…In addition, we have demonstrated that similar changes occur in patients with recurrent VVS. The conclusion of Leftheriotis et al 17 that dynamic CA is preserved in normal subjects at low levels of orthostatic stress is similarly supported by our initial data after head-up tilt, which also demonstrate similar preservation of dynamic CA in patients with recurrent VVS.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, we have demonstrated that similar changes occur in patients with recurrent VVS. The conclusion of Leftheriotis et al 17 that dynamic CA is preserved in normal subjects at low levels of orthostatic stress is similarly supported by our initial data after head-up tilt, which also demonstrate similar preservation of dynamic CA in patients with recurrent VVS.…”
Section: Discussionsupporting
confidence: 87%
“…27 More recently, Leftheriotis et al 17 used rapid thigh-cuff deflation to demonstrate preserved dynamic CA in normal subjects 5 minutes after 40°head-up tilt. In many ways, this study forms a link between the studies of Zhang et al 19 and Leftheriotis et al 17 and shows that the findings of all 3 studies are compatible with each other. The finding of Zhang et al 19 that dynamic CA deteriorates in normal subjects during presyncope is supported by our demonstration of decreased ARI values during presyncope in the syncopal control group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, a paradoxical cerebral vasoconstriction in healthy (5,6,22,38) and orthostatically intolerant (13,14) individuals has been reported during postural stress and LBNP. However, our previous work (38), as well as that of others (8,21), showed that cerebral autoregulation remains intact during HUT in healthy subjects, suggesting that decreases in perfusion pressure were unlikely to be the cause of the decrease in cerebral flow. Similarly, analysis of transfer function gain between CFV and blood pressure found no change in gains during tilt in these subjects (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…The latency in dCA as derived from spontaneous MAP decreases provides confirmatory information regarding impaired CA, as well as produced data akin to rapid thigh-cuff deflation as a stimulus for dCA. 13 CA in stroke is controversial. In large MCAS, a transient rise in BP by phenylephrine raises MCA V mean on the affected side only, indicating unilaterally impaired static CA.…”
Section: Discussionmentioning
confidence: 99%